Meningkatkan Motivasi Belajar Peserta Didik Dengan Menggunakan Metode Guided Inquiry (Inquiry Terbimbing) Pada Konsep Gerak di Kelas X SMA Negeri 3 Halmahera Timur - Kartini Lana (Peneliti.net, 2022)
The type of research used is classroom action research, which aims to determine whether the application of the Guided Inquiry Learning Model can increase the learning motivation of students in class X SMA Negeri 3 East Halmahe and how it is applied to the concept of motion. The research subjects were students of class X science at SMA Negeri 3 East Halmahera with a total of 28 students consisting of 1 class. This research was carried out in 2 cycles consisting of 4 components, namely: Planning, Implementation, Observation and Reflection. The results showed that the application of the Guided Inquiry learning model in cycle I and cycle II could be seen from the initial conditions before the average action, after the research in the first cycle only reached 30%, and after doing the research the second cycle the percentage of students' mastery results increased to 50%. The Guided Inquiry Learning Model can increase students' learning motivation, the first cycle of students' learning motivation reaches 50% in the pretty good category and the second cycle reaches 50% very well, this shows that the students' learning motivation in cycle I increases in the second cycle with a very good category. . Thus, it can be concluded that the use of the Guided Inquiry learning model can increase the learning motivation of students in class X IPA-1 SMA Negeri 3 East Halmahera.